Comparison of Early Retinal Microvascular Changes and Microalbuminuria as Indicators for Increased Cardioascular Risk - Huchzermeyer, Cord; Schaller, Barbara; Schmid, Kathrin; Schmieder, Roland; Michelson, Georg (Klinische Monatsblätter für Augenheilkunde, 2011)
Prevention of cardiovascular disease is an important goal in clinical medicine and public health. In the process, the diagnosis of early end-organ damage is a priority beside the treatment of classic cardiovascular risk factors. To achieve this, the ophthalmoscopic examination of the retinal vessels plays a prominent role. Alternatively, the quantification of low quantities of albumin in the urine (microalbuminuria) allows the detection of early vascular damage in the kidney. The question is addressed as to whether these two methods are interchangeable or are rather complementary.We examined 226 members of the staff of the University Hospital Erlangen who volunteered to participate in a preventive campaign. A comprehensive history was taken, and height, weight and blood pressure were measured. Analysis of serum lipids and determination of the urinary albumin/creatinine ratio were performed. Fotos of the central fundus were taken with a non-mydriatic camera and analysed by an experienced ophthalmologist in a standardised fashion. The risk for cardiovascular mortality within the next ten years was estimated from age, sex, blood pressure and serum cholesterol using the euroSCORE tables for Germany.There was no signficant correlation between the arteriovenous ratio of the retinal vessels and the urinary albumin/creatinine ratio. Neither parameter correlated with the euroSCORE Germany. Arteriovenous crossings and focal narrowing of the retinal vessels were associated signficantly with an elevated euroSCORE risk.In large population-based studies, the arteriovenous ratio and the urinary albumin/creatinine ratio have been confirmed as markers of cardiovascular risk. In our study, there was no correlation between these two parameters. Thus, they seem to present independent risk markers. The presence of arteriovenous crossings and focal narrowing seems to be linked more closely to the classic cardiovascular risk factors from which the euroSCORE is calculated. The ophathlmolscopic examination of retinal vessels and the analysis of urinary albumin/creatinine ratio seem to complement rather than replace each other.
EVALuna2:3434